Transcatheter aortic valve implantation—2014 update. Issue 1 (December 2015) - Phang, E. H. Q.; Tay, E.; Hon, J. K. F.
Abstract: There is a growing trend for high‐risk patients with severe aortic stenosis who are denied open heart surgery to undergo transcatheter aortic valve implantation (TAVI). Since its invention more than two decades ago, TAVI has evolved rapidly from the proof‐of‐concept phase to become an established Food and Drug Administration‐approved technology. This article reviews the developmental histories and current status, as well as the future advancement of the technique. Answer questions and earn CME: https://www.wileyhealthlearning.com/Activity2/3707283/Activity.aspx